1975
DOI: 10.1159/000240758
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Increased Fatty Acid Transfer across the Placenta during a Maternal Fast in Rabbits

Abstract: Fetal rabbits were obtained by Caesarian section from 28-day pregnant does which had been fasted for 48 h (days 26–28). Organ weights, fat contents and blood metabolite levels were compared with a group obtained in a similar manner from non-fasted does. Similar data were obtained for term fetuses (31 days) born by natural delivery. In 28-day pregnant, fasted does, blood levels of free fatty acids (FFA) and glycerol were doubled compared with non-fasted controls. Fetal levels showed a similar increase. Both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…In the present study, the rabbits did not increase food intake throughout pregnancy (Fig. 2) in agreement with previous data (6,21,42). In fact, food intake was reduced by about 15% for the last 4 days of gestation, similar to the rat in which the food intake drops by 15-20% 2 days before term (10,20,38).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the rabbits did not increase food intake throughout pregnancy (Fig. 2) in agreement with previous data (6,21,42). In fact, food intake was reduced by about 15% for the last 4 days of gestation, similar to the rat in which the food intake drops by 15-20% 2 days before term (10,20,38).…”
Section: Discussionsupporting
confidence: 94%
“…This indeed may have been a complicating factor and we did not control for it, though we think its significance is minor relative to the size of the effect we observed (no increase in FFA for the first 2 h after the DEX injection; a 13-fold increase in FFA 30 min after the ACTH injection). In contrast, in an experiment by Edson et al (1975), fasting female rabbits for 48 h resulted in only a 2-fold increase in FFA levels. Thus we think the length of the fasting our rabbits experienced was too short to have had a significant impact on our results.…”
Section: Discussionmentioning
confidence: 76%
“…In previous investigations (Edson et al 1975;Elphick et al 1976) we demonstrated a rapid flux across the placenta of FFA with prevailing maternal levels determining the net flow to the foetus. This investigation has extended these observations by examining the differences in the transport across the rabbit placenta of the main fatty acids present in foetal adipose tissue.…”
Section: Checking Experimentsmentioning
confidence: 75%